Algeria Investment Climate Assessment - World Bank (Washington, DC, 2013)
This investment climate assessment is part of a series of analytical works on prepared by the World Bank with the aim of laying out the basis for the elaboration of the Bank's country assistance strategy for the country. It is based on three pieces of work undertaken in parallel in Algeria between January 2002 and march 2003: an investment climate survey of 562 Algerian firms, policy work resulting from a series of four missions to Algeria; and a foreign investors survey of 57 European investors from France, Italy and Spain. The report is organized as follows: chapter I gives a general background of the main macroeconomic issues in Algeria, recent developments, and a brief description of the enterprise sector. Chapter II presents the main findings of the ICA survey, with a particular focus on differences among types of firms (size, ownership, sector and age). It also estimates the effect of the investment climate on productivity and wages. Summaries of the main institutional issues and policy recommendations complement the quantitative assessments of the constraints. In each area, international comparisons are presented, based on similar surveys in other countries or other sources. It also includes a summary of the findings of the potential foreign investors survey. Chapter III builds on the survey evidence to identify the priority institutional reforms needed to improve the investment climate in Algeria. As a result, a short to medium term strategy for private sector development is proposed, which includes a detailed set of reform actions.